Dibenzazepine Attenuates Against Cisplatin-Induced Nephrotoxicity in Rats: Involvement of NOTCH Pathway - Rana H. Abd El-Rhman; Reem N. El-Naga; Amany M. Gad; Amany M. Gad; Mariane G. Tadros; Sherifa K. Hassaneen (Frontiers Media S.A., 2020)
Cisplatin is one of the standard anti-cancer agents that are used to treat variety of solid tumors. Nevertheless, due to the accumulation of cisplatin in the renal epithelial cells, nephrotoxicity was found to be the main side effect that limits its clinical use. The current study was conducted to assess the potential nephroprotective effect of dibenzazepine, a Notch inhibitor, against cisplatin-induced nephrotoxicity in rats as well as the possible mechanisms underlying this nephroprotection. The rats were pre-treated with 2 mg/kg dibenzazepine for 7 days before giving a single nephrotoxic dose of cisplatin (7 mg/kg). Cisplatin induced acute nephrotoxicity, where blood urea nitrogen and serum creatinine levels were significantly increased. Besides, lipid peroxidation was markedly elevated and the levels of reduced glutathione and catalase were significantly reduced. Also, the tissue levels of the pro-inflammatory mediators; IL-1β, TNF-α, and NF-kB, were significantly increased in the cisplatin group. The pre-treatment with dibenzazepine significantly mitigated the nephrotoxic effects of cisplatin, the oxidative stress and inflammatory status as well as decreased caspase-3 expression, as compared to the cisplatin group. Furthermore, the up-regulation of Notch-1 and Hes-1 was found to be involved in cisplatin-induced nephrotoxicity and their expression was significantly reduced by dibenzazepine. The nephroprotective effect of dibenzazepine was further confirmed by the histopathological assessment. Moreover, dibenzazepine pre-treatment of hela and PC3 cells in vitro did not antagonize the cisplatin anti-cancer activity. In conclusion, these findings show that dibenzazepine provides protection against cisplatin-induced nephrotoxicity. Moreover, the up-regulation of the Notch pathway was shown to play a role in the pathogenesis of cisplatin-induced renal injury.